ISIS in Horn of Africa: An Imminent Alliance with Al-Shabaab? - Syed Huzaifah Bin Othman Alkaff (2016)
The Islamic State in Iraq and Al-Sham (ISIS) is expanding into Somalia with factions of the Al Shabaab militant groups pledging allegiance to its “caliph” Abu Bakar Al Baghdadi. Will these defections split the Al Qaeda-affiliated Al Shabaab or empower IS in the Horn of Africa?